Concomitant use of elastic suture associated with vacuum dressing in the closure of large soft tissue losses - Antoninho José Tonatto; Jorge Luis de Moraes; Caio Munaretto Giacomazzo; Alessandra Bossardi; Marlon Câmara Lopes; Renato da Silva Freitas (Revista Brasileira de Cirurgia Plástica, 2022)
Treating complex wounds with great loss of soft tissues is a challenge for plastic surgery, especially when the wound is infected. Several options are considered for treatment, such as sutures, grafts, flaps, and expanders. Due to the complexity of the cases, the frequent association of morbidities, the need for multidisciplinary interventions, and long hospital stays, treatment costs are often high. This work demonstrates the elastic suture technique used in a clinical case, using continuous skin traction in association with a vacuum dressing, which enabled patient rehabilitation without the need for more aggressive interventions to close the extensive traumatic wound.